All Days 2012
DOI: 10.2118/154209-ms
|View full text |Cite
|
Sign up to set email alerts
|

Secondary and Tertiary Recovery of Crude Oil from Outcrop and Reservoir Rocks by Low Salinity Waterflooding

Abstract: A wide range of outcrop sandstones and carbonates have been tested for waterflood response to one twentieth dilution of synthetic seawater, using a single crude oil that gave high response to low salinity flooding for a reservoir rock. The tested outcrop rocks included 17 sandstones and 6 carbonates. Gas permeabilities ranged from 1.49 to 7,187 mD and porosities from 10 to 39%. The average reduction in residual oil for tertiary response was only 1.5% OOIP with the highest being 5.8% OOIP; some rocks showed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…However, there is a pressing need to develop cost-effective techniques to enhance oil recovery in the period of low oil prices. Engineering the injected water chemistry and using water wisely to enhance oil recovery is a novel and emerging research area, which is called low salinity water flooding [4][5][6][7], smart water flooding [8][9][10][11][12], designer water flooding [13][14][15][16], or ion tuning water flooding [17,18]. Many researchers found that low salinity water injection could achieve an incredible additional oil recovery in sandstone and carbonate reservoirs from both experiments and field tests [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a pressing need to develop cost-effective techniques to enhance oil recovery in the period of low oil prices. Engineering the injected water chemistry and using water wisely to enhance oil recovery is a novel and emerging research area, which is called low salinity water flooding [4][5][6][7], smart water flooding [8][9][10][11][12], designer water flooding [13][14][15][16], or ion tuning water flooding [17,18]. Many researchers found that low salinity water injection could achieve an incredible additional oil recovery in sandstone and carbonate reservoirs from both experiments and field tests [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cores particles solely containing different clay types, such as kaolinite, illite, chlorite and montmorillonite, have been reported to show similar electrostatic behavior with quartz-dominated Berea sandstones [56,180]. In several other studies (like [33,38,116]), it was reported that sandstone reservoir rocks responded better to low saline brine than outcrop rocks, which demonstrated that different sources of sandstone show varying responses to brine-dependent recovery due to different pore geometries and grain structures [168].…”
Section: Sandstone Rocksmentioning
confidence: 87%
“…The earliest comprehensive study undertaken by Morrow and colleagues [11][12][13][14]86,87] demonstrated the effect of oil-brine-rock interactions on improving oil recovery in a clay-rich rock formation and presented additional oil recovery from the brine-dependent process due to salinity gradient and wettability shift. Since then, numerous studies have been conducted with most tests showing positive results [13,21,[23][24][25][26][27][28][29][30][31][32][33][34], while no response was observed in other tests [28,[36][37][38][39][40].…”
Section: Laboratory Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible to observe improved water-wetness due to low saline brine injection on quartz grain, but presence of clays can either increase pore surface charge or provide a higher surface area and an anchor point for the oil compounds to further increase the effect of wettability changes. In addition, cores partcles solely containing different clay types, such as kaolinite, illite, chlorite and montmorillonite, has been reported to show similar electrostatic behavior with quartz-dominated Berea sandstones [124,125] In several other studies, it was reported that sandstone reservoir cores responded better to low saline brine than outcrop cores [43,60,126], which demonstrated that different sources of sandstone shows varying responses to brine-dependent recovery due to different pore geometry and grain structure [107]. Carbonate rocks On the other hand, carbonate rocks are primarily composed of calcite (CaCO3) and dolomite (CaMg(CO3)2), with variety of other minerals like anhydrite/gypsum (CaSO4), magnesite (MgCO3), Aragonite (CaCO3), apatite (phosphate source), quartz, siderite (FeCO3), evaporite, pyrite, etc.…”
Section: Sandstone Rocksmentioning
confidence: 94%